(untitled) (Indian Journal of Animal Production and Management, 2025)
A field study was conducted in Banaskantha district of Gujarat to know the calf rearing practices followed by Kankrej cattle owners. Three tehsil were purposively selected where highest Kankrej cattle population and four villages were selected randomly from each tehsil. Ten respondents from each of village were selected thus making a sample of 120 Kankrej cattle owners. The study revealed that majority of the respondents (95.83 per cent) attended calving and care of the calves after parturition. Majority 81.67 per cent of respondents did not followed practice of ligation and disinfection of the navel cord. All the respondents followed practice of feeding colostrum to new born calves but only 21.67 per cent of the respondents fed colostrum to new born calves within one to two hour of birth. More than half (63.33 per cent) of cattle keepers did not perform deworming practices in calves. Only 32.50 per cent respondents provided jacketing as well as bedding on litter during winter to protect calves from cold and majority (79.17 per cent) of respondents vaccinate their calves against disease and isolate the sick animals from healthy ones.